International Evidenceon Tradables and Nontradables Inflation - Wolf, Holger (IMF Working Papers; Working Paper ;, 1994)
Using 1970-85 sectoral data for the OECD we find that inflation in nontradable good exceeds inflation in tradables. We identify a demand shift towards nontradables and faster growth of total factor productivity in the tradable goods sector as the prime causes of the differential inflation. In addition, disinflation attempts and the exchange rate regime appear to have exerted significant influence on the relative inflation rate.